Amino acid Substitution Mutations Analysis of gyrA and parC Genes in Clonal Lineage of Klebsiella pneumoniae conferring High-Level Quinolone Resistance - Amin Norouzi; Omid Azizi; Hossein Hosseini; Samane Shakibaie; Mohammad reza Shakibaie (Pasteur Institute of Iran, 2014)
Background: Emergence Klebsiella pneumoniae resistant to quinolone antibiotics due to mutations in gyrA and parC genes created problem for treatment of patients in different hospitals in Iran. The objective of this study was to determine the amino acid substitutions of GyrA and ParC proteins in certain clonal lineages of the K. pneumoniae conferring high level quinolone resistance. Methods: One hundred and eleven isolates of K. pneumoniae were recovered from clinical specimens in a teaching hospital in Kerman, Iran. The antibiotic susceptibility and MIC of quinolones were determined according to CLSI guidelines. Clonal lineages of the isolates were determined by enterobacterial repetitive intergenic consensus (ERIC)-PCR amplification using ERIC specific primer sequences. Amino acid mutation profile of gyrA and parC amplicons of six high quinolone resistant isolates was also investigated by DNA sequencing. Results: Twenty two isolates were resistant to nalidixic acid (MIC 256µg/ml), ciprofloxacin (MIC 32µg/ml), levofloxacin (MIC 32µg/ml), and ofloxacin (MIC 32 µg/ml). Typing by ERIC-PCR identified 4 clusters and six singleton, the largest one was belonged to cluster-3 obtained from urine samples. Sequencing of gyrA gene showed three amino acid substitutions (Ser83→Ile Lys154→Arg Ser171→Ala) in the strains 18, 20, 33, two mutations (Lysine154→Arg Ser171→Ala) in the strains 27, 65 and six substitutions in the strain 66, of which, three (Ser83→Phe Asp87→Ala Val190→Gly) were unique for this strain. Sequencing of parC gene revealed double substitutions (Ser129→Ala Ala141→Val) in the strains 18, 27, 66 and three aminoacid changes (Ser80→Ile Ser129→Ala Ala141→Val) in the strains 20 and 33 respectively. Alignment and phylogenetic tree analysis of the gyrA sequence from highly quinolone resistant isolate 66 with homologs sequences obtained from the NCBI database confirmed 99.8% similarity to gyrA gene of the K. pneumoniae ha10 (GenBank: JX123017.1). Conclusion: The results of present study suggest that acquisition of mutations in certain positions of gyrA and parC genes confer high level resistance to quinolones.